New record of genus Gaucha Mello-Leitão, 1924 (Solifugae: Mummuciidae) in Argentina - Zubarán, Gastón Enrique (2020)
The family Mummuciidae Roewer, 1934 comprises twenty-seven known species of solifuge in the southern hemisphere of the New World, divided into eight genera (González Reyes and Carronca, 2013; Botero Trujillo et al., 2017; 2019a, b). Is the only family in the region whose members exhibit diurnal habits (Maury, 1984; Botero-Trujillo et al., 2019a). In Argentina, the family is represented by six genera: Cordobulgida Mello Leitão, 1938; Curanahuel Botero-Trujillo, 2019b; Gaucha Mello Leitão, 1924; Mummucia Simon, 1879; Mummucina Roewer, 1934; and Uspallata Mello Leitão, 1938; with a total of eight species. Within the genus Gaucha, eleven species are described (Botero-Trujillo et al., 2019a), distributed in Brazil (six species), Bolivia (one species), Uruguay (one specie) (BoteroTrujillo et al., 2017, 2019a). In Argentina, only two species are known: Gaucha casuhati Botero Trujillo et al., 2017, from the province of Buenos Aires, and Gaucha ramirezi Botero-Trujillo et al., 2019a, from the provinces of Córdoba and Santiago del Estero. With the new locality record for the genus Gaucha presented here, they would add a total of three species present in the country.